The Effect of soil inoculation with bio-fertilizer AMF (Arbuscular Mycorrhizae Fungi( on some morphological and productive characters of potato plants ( Solanum tuberosum. L) cultivated in the spring season. (Latakia University Journal -Biological Sciences Series, 2022)
The research was carried out in the gardens nursery of Tishreen university in the spring (2020),within net plastic bags, and used in the research, sandy clay soil.The design of randomized complete sectors was adopted in the implementation of the research, which aimed to study the Effect of soil inoculation  with bio-fertilizer ( AMF) (Arbuscular Mycorrhizae Fungi ) while reducing the recommended amount of mineral fertilizers from nutrients (N, P,K) in different proportions (0 , 25, 50%) , Treating the farmer by adding the full amount of mineral fertilizers recommended on some morphological and productive characteristics of potato plants. the results showed that soil inoculation  with bio-fertilizer (AMF) had a positive effect in stimulating the growth of potato plants in terms of increasing leaves number ,leaf area,plant height, tuber weight, plant production and marketing production quantity compared with the control,and adding 25% ,50% of the recommended amount of mineral fertilizers contributed to a significant increase in all the studied traits, with the superiority of the bio-fertilizer treatment with 50% of the amount of  recommended mineral fertilizers significantly over all treatments and without significant differences with the treatment of farms, thus the effective role of soil inoculation with biofertilizer (AMF) is evident in reducing the amount of mineral fertilizers(50%)while increasing productivity .